The Linguistic Allegory and Reproducing Lexical Meaning in Kurdish Language - Ahmed, Ara A.; Qassem, Huda A. (Humanities Journal of University of Zakho, 2018)
The subject of this research is the linguistic allegory and reproducing lexical meaning in Kurdish language, through this subject the development and changing the meaning and the role of the linguistic allegory are the main headlines in this research. The allegory is the process of the creation and creativity in language, is an important source to get the units meanings in languages and it is considered as an important factor in the development of meaning. The linguistic allegory is the main angle in language and it has a good role in developing the words meaning, and this is the most important subjects that deal with the science of meaning, the aim of this research to probate that the allegory of linguistic and its role to reproduce new meaning in Kurdish language is a rich way, especially in Badinan Dialects and it is geographical limits in this research and because Duhok city is considered the language center in this dialect. For this, we take the practical examples from the language lexical is the center of Duhok City and also the aim of this research to insist on that this dialect like all the other languages exposures development and this change is according to some laws and exposures the language with all its levels and especially the meaning level, and in this research the importance of linguistic allegory and the result of reproducing the lexical words and we don't care about the practical allegory in eloquence.